Zdroje a šíření vybraných komodit keramické produkce vrcholného a pozdního středověku - Hložek, Martin (Masaryk University Press, 2021)
Title in English: Sources and Distribution of Selected High and Late Medieval Pottery Products. The publication is focused on late medieval pottery products with higher aesthetical effect. The key group is represented by stove tiles, where the unifying elements of relief decoration helped to define series of motifs for stoves with specific iconographic concept, which were found in various locations. The same approach can be also used with small ceramic sculptures, aquamaniles and relief-decorated floor tiles, even though the achieved information value in these cases is much lower. Micropetrographic, XRF and other analyses helped to identify the production centres and the distribution model of these ceramic groups. 3D documentation enabled a detailed comparison of differences between individual reliefs and specific traces of manufacturing procedures. Individual chapters contain active links to the source database of analysed items and to 3D models of selected specimens from reference collections.